Study to assess knowledge, attitude on organ donation among medical students in a medical college, Telangana, India - Priyanka, S.; Singh C., Sunil Pal; Reddy, P. Narsimha (International Journal Of Community Medicine And Public Health, 2019)
Background: Organ donation rate in India is only 0.26 per million. This is mainly due to lack of knowledge about the need of organ donation. Health care professionals play a vital role in imparting positive knowledge regarding organ donation. Methods: Institutional based cross sectional study was conducted among 1st year MBBS students (n=135). Data was collected and pre and post analysis was done using a pre-validated self-administered questionnaire. Data was entered in Ms Excel and analysed using SPSS 17 software. Results: Media was found to be most common source of information regarding organ donation. 91.1% support organ donation. 78.5% have not heard about donor card. Only 34.6% have heard about jeevandan scheme. 77.8% participants has knowledge that brain death is irreversible and 65.9% students believe that there is age limit for organ donation. 87.4% has adequate knowledge that single donor can donate to multiple recipients and 95.6% students believe that organs should not be donated from persons who has cancers or HIV. Conclusions: From the data analysed it is evident that there was a significant increase in knowledge following Awareness session on organ donation. Many have a positive attitude towards organ donation.